2019
DOI: 10.1103/physrevd.99.104065
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a Reissner-Nordström-AdS black hole under perturbations of a scalar field coupled to the Einstein tensor

Abstract: We study the instability of a Reissner-Nordström-AdS (RNAdS) black hole under perturbations of a massive scalar field coupled to Einstein tensor. Calculating the potential of the scalar perturbations we find that as the strength of the coupling of the scalar to Einstein tensor is increasing, the potential develops a negative well outside the black hole horizon, indicating an instability of the background RNAdS. We then investigate the effect of this coupling on the quasinormal modes. We find that there exists … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Rotating Kerr black holes may also be superradiantly unstable under massive scalar perturbation, where the mass of the scalar provides a natural mirror [16][17][18][19][20][21][22][23][24][25]. If a mirror-like boundary condition is imposed outside the black hole horizon or if the RN/Kerr black hole is asymptotically non-flat, the black hole is superradiantly unstable in certain parameter spaces [26][27][28][29][30][31]. Besides scalar perturbations, a massive vector perturbation on a rotating Kerr black hole has also been discussed [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Rotating Kerr black holes may also be superradiantly unstable under massive scalar perturbation, where the mass of the scalar provides a natural mirror [16][17][18][19][20][21][22][23][24][25]. If a mirror-like boundary condition is imposed outside the black hole horizon or if the RN/Kerr black hole is asymptotically non-flat, the black hole is superradiantly unstable in certain parameter spaces [26][27][28][29][30][31]. Besides scalar perturbations, a massive vector perturbation on a rotating Kerr black hole has also been discussed [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…When a mirror is introduced, superradiant modes are supported and the stringy RN black hole becomes superradiantly unstable under charged massive scalar perturbation [30][31][32]. It is also found that extra coupling between the scalar field and the gravity can result in superradiant instability of RN/RN-AdS black holes [33,34].…”
Section: (): V-volmentioning
confidence: 97%
“…The QNMs and QNFs have been calculated using various numerical and analytical techniques [57][58][59][60][61][62]. In the case of gravitational perturbations it was found that for the Schwarzschild and Kerr black hole background the longestlived modes are always the ones with lower angular number .…”
Section: (): V-volmentioning
confidence: 99%